2012
DOI: 10.2174/092986712803341476
|View full text |Cite
|
Sign up to set email alerts
|

Ligands for Fluorescence Correlation Spectroscopy on G Protein-Coupled Receptors

Abstract: G protein-coupled receptors (GPCRs) comprise a large protein family of transmembrane receptors involved in many physiological processes. They are engaged in various transduction processes of extracellular signals into intracellular responses. Due to their involvement in numerous diseases they represent an important pharmacological target. Fluorescence correlation spectroscopy (FCS) poses a very sensitive analytical technique well-suited for the investigation of GPCRs. It is minimally invasive and operates on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 34 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…Fluorescence is one of the most sensitive spectroscopic methods and many fluorescent ligands have been reported for locating G-protein-coupled receptors (GPCRs), for studying ligand/receptor interactions, and more generally for better understanding their pharmacology and physiological process. The history of fluorescent ligands is linked to the development of commercially available fluorophores. Organic dyes have been designed and synthesized to exhibit excitation and emission wavelengths, which are compatible with biological observation and are associated to ligands in conjugation reactions.…”
mentioning
confidence: 99%
“…Fluorescence is one of the most sensitive spectroscopic methods and many fluorescent ligands have been reported for locating G-protein-coupled receptors (GPCRs), for studying ligand/receptor interactions, and more generally for better understanding their pharmacology and physiological process. The history of fluorescent ligands is linked to the development of commercially available fluorophores. Organic dyes have been designed and synthesized to exhibit excitation and emission wavelengths, which are compatible with biological observation and are associated to ligands in conjugation reactions.…”
mentioning
confidence: 99%
“…FCS has been used to measure the diffusion and size of nucleic acids, lipids, individual proteins, and protein complexes in live cells. Recent examples of processes investigated with FCS/ FCCS include viral capsid assembly, mRNA diffusion, enzyme subunit dissociation, system wide measurements of protein diffusion in yeast, gene expression profiles, protein-lipid interactions, and receptor-ligand interactions [52][53][54][55][56][57][58][59][60]. FCCS can be used to quantify and distinguish different populations of receptors, protein complexes, protein-lipid interactions, and protein-DNA interactions [61][62][63][64][65][66][67][68][69].…”
Section: Fluorescence Correlation Spectroscopy (Fcs)mentioning
confidence: 99%
“…Fluorescent GPCR ligands have been used for studies ranging from localization of receptors in tissues and cells (including an early demonstration of the internalization of ligand-bound receptors in cells [53]), to simple binding assays (in many cases, as replacements for radioligands), to sophisticated probing of the geometry and mechanisms of ligand-receptor interactions and receptor-receptor interactions. Several previous reviews have provided compendia of fluorescent ligands for GPCRs that have been reported in the literature [29, 5561]. Table 1 presents an updated list of published fluorescent ligands for GPCRs, including information from these previous reviews.…”
Section: Fluorescent Ligandsmentioning
confidence: 99%